The material's relevance - Labarta Aizpún, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
Architects, perhaps busy on other tangent knowledge to the field of architecture, have overlooked the cognitive power of the gaze as a purveyor of the information accumulated in the material. Not for nothing architecture strives to sort out the matter and with it the whole world around. We not only need it in order to shape the spaces where man lives but in fact they find their origin in matter itself. Hence in order to insure consistency the architectural work should not spring from images but from materials and from the way these are related. The very path of architectural history can be perceived as an evolution of the constructive systems that, at the same time, are a consequence of the revolutions derived from the different use of materials.Modern masters understood that from matter emanated the possibility of the creation of a new order, and not only they did not look down on it but to its deep knowledge, mechanic and plastic, assigned their sleeplessness, aware that with its order they could infer a stream that could, essentially, organize the world. They required the measurable matter to reach the order of the spirit.Likewise the material supplies the information for the expression of the architectural project. The composition factors of the project find their reason in the measures and the expressive values of the materials as well as in the way in which they gather. In this issue of the journal those investigations based in the equivalence of the design, constructive and aesthetic decisions can find adaptation. That is, the architectural exercises which begin and end in the metric and sensitive experience of the material. The material can be equally understood as a repository of the memory of the places upon which the landscape is built. The examples are numerous where the essential construction of the landscape refers to the accumulated memory in the materials. Even some modern architects’ careers found a turning point or inflection starting from a modification in the perception and use of the materials. The search of a timeless and universal architecture is closely related with the perceptive and significant values emanated from the material.The development of new technologies, as well as the growing influence of scientific research in contemporary thinking, has opened the possibility of incorporating new arguments to the discussion and elaboration of the architectural fact from a new perspective of materiality. A perception that includes the transposition to architecture of new strategies which imply lightness, levity, transparency, dematerialization and that, inescapably, are based in investigations about new material possibilities. Similarly the incorporation of new materials, as well as their recycle, offers new formulas in the sphere of construction that, according to a new contemporary sensibility, may extend the consistency of the architectural discourse.This fourth edition of our journal pretends to convene those investigations that make inquiries in the material – in its constitution, in its plastic and mechanic values ‒ as the reason for the construction of a landscape, the measure and the halo for a composition or the argument upon which rests the reason of the architectural project.Carlos Labarta Aizpún